THE EFFECTS OF DIFFERENT SPACINGS AND PHOSPHORUS APPLICATION ON THE GROWTH AND YIELD OF COWPEA (VIGNA INGUICULATA)L) (WALP) - REMISON, S.U.; BELLO , B.; OKUNARIWO, T. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Cowpea cv. Prima was grown at six densities and three P. levels in experiments made over three seasons in 1974 and 1975. In all experiments, number and weight of pods per plant decreased with increase in density whilst number and weight of pods per m2 and grain yield increased linearly with density. Weight of haulms and total dry matter yield also increase with density. P generally promoted vegetative growth and in the early season of 1975 it delayed flowering significantly. There was significant Px density interaction in the early season of 1975 for weight per pod, harvest index and weight of pods per plant and per m2.